Developing Digital Teaching Identities? The Role of Initial Teacher Education (Practicum) - Maslin, Peter (Auckland University of Technology, 2025)
This PhD research examines how the voices of pre‐service teachers can reshape policymaking conversations about digital technologies in education and the digital identities these teachers are expected to adopt. In an era when the quality of pre‐service teachers is under intense scrutiny, Initial Teacher Education (ITE) faces mounting pressure to deliver classroom-ready teachers from day one. Rather than reducing pre‐service teacher digital identity to a commodified product, this study foregrounds the authentic narratives of pre‐service teachers, empowering them to maintain control over their evolving digital selves. The research investigates the pivotal role of lived practicum experiences in shaping pre‐service teachers’ digital identities. By drawing on narrative theory and conducting semi-structured interviews, the study uses thematic analysis to listen to how pre‐service teachers negotiate, adjust, and navigate their digital identities during practicum experiences. The resulting insights challenge fixed, risk-free interpretations of digital technologies and identities in education, arguing instead that both are intricately woven into everyday life and are in a constant state of evolution. Furthermore, this work highlights the importance of incorporating pre‐service teacher voices into ITE practices. Creating spaces for storytelling humanises digital identities and equips pre‐service teachers with the agency to resist pre-determined digital coding. Although situated within a specific ITE context, the findings provide a forward-thinking blueprint for ITE providers aiming to support, empower, and learn from the dynamic digital experiences of pre‐service teachers.